2010
DOI: 10.1111/j.1911-3846.2010.01021.x
|View full text |Cite
|
Sign up to set email alerts
|

The World Has Changed—Have Analytical Procedure Practices?*

Abstract: Analytical Procedures (APs) provide a means for auditors to evaluate the ''reasonableness'' of financial disclosures by comparing a client's reported performance to expectations gained through knowledge of the client based on past experience and developments within the company and its industry. Thus, APs are fundamentally different than other audit tests in taking a broader perspective of an entity's performance vis-a`-vis its environment. As such, APs have been found to be a cost-effective means to detect mis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
62
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 156 publications
(67 citation statements)
references
References 17 publications
4
62
0
1
Order By: Relevance
“…Hirst and Koonce (1996) documented that auditors in the past did not use non-financial data and information during the performance of analytical procedures. Trompeter and Wright (2010) extended the work of Hirst and Koonce (1996) and mentioned that auditors reported moderate use of non-financial data and information during the performance of analytical procedures, but still prefer to depend on prior years account balances when developing expectations for current year account balances. Brazel et al (2014) documented that only a minority of senior auditors choose to depend on non-financial measures when evaluating revenue account balances via analytical procedures.…”
Section: The Role Of Non-financial Data and Information In Verifying mentioning
confidence: 96%
See 4 more Smart Citations
“…Hirst and Koonce (1996) documented that auditors in the past did not use non-financial data and information during the performance of analytical procedures. Trompeter and Wright (2010) extended the work of Hirst and Koonce (1996) and mentioned that auditors reported moderate use of non-financial data and information during the performance of analytical procedures, but still prefer to depend on prior years account balances when developing expectations for current year account balances. Brazel et al (2014) documented that only a minority of senior auditors choose to depend on non-financial measures when evaluating revenue account balances via analytical procedures.…”
Section: The Role Of Non-financial Data and Information In Verifying mentioning
confidence: 96%
“…Examples of sources of information that may be approached by an auditor include asking other members of the audit team, generating self-explanations, checking prior years' work papers, and inquiring the client personnel. Results of Hirst and Koonce (1996), as well as Trompeter and Wright (2010), indicated that client personnel inquiry is the primary source of information used by auditors to find explanations for unexpected results got from analytical procedures during the planning of an audit. Of course, this would be a matter of concern if auditors do not subject the explanations of the client personnel to further investigation to check its reasonableness.…”
Section: The Importance Of Understanding the Business Environment Of mentioning
confidence: 99%
See 3 more Smart Citations